THE COMBINATION OF AHP AND TOPSIS METHODS IN DETERMINING THE RANKING OF RECOMMENDATIONS FOR IMPROVEMENT OF INFORMATION TECHNOLOGY SERVICES - Fitrani, Laqma Dica (LPPM Universitas Nusa Mandiri, 2021)
In order to improve the quality of information technology unit, XYZ University has to measure and improve the services based on a best practice framework. ITIL 3rd version was chosen to determine the service level of this unit. ITIL V3 was focused on two domains, specifically Service Operations to measure the service improvements problems and Continual Service Improvement to establish improvement continously. The measurement showed that the maturity level of IT services in the information technology unit on the Service Operation domain was at level 3 and Continual Service Improvement was at level 2, and each gap value was 1.5 and 1, respectively. The level calculation resulted in 14 recommendations that must be applied by information technology unit of XYZ University. The recommendations were applied by implementing a decision making system use the combination of AHP and TOPSIS method. AHP was needed to decide the weights of the predetermined criteria, while TOPSIS was used in calculation to rank the available alternatives. The top to bottom ranking of the 14 recommendations was Service Operation Processes, CSI Methods and Techniques, Implementing CSI, Organizing for CSI, Service Management as a Practice, Service Operation Technology Consideration, CSI Technology Considerations, CSI Processes, Common Service Operation Activities, Organizing Service Operations, CSI service Management as a Practice, CSI Principles, Service Operation Principles, and Implementing Service Operations.